Effects of Class-Wide Choice Making on the Behaviour of Students with Mild Intellectual Disability. Issue 1 (2nd January 2022) - Tounsi, Olfa; Masmoudi, Liwa; Trabelsi, Khaled; Koubaa, Abdessalem; Clark, Cain; Anouda, Chourouk; Bahloul, Mourad
ABSTRACT: In general, behavioural intervention is a more effective form of treatment. By the way, several behavioural interventions were studied in the education field to support and prevent students' behaviour among them choice making. An ABAB withdrawal design was used to examine the effects of class-wide choice making on the engagement and disruptive behaviours of 12 students with mild intellectual disability enrolled in a two self-contained physical activity classes. Intervention was implemented in an ordinary context and applied at the class-wide level by applying a curricular modification. To measure the variables studied, direct observation was used to collect data from videos of filmed sessions by applying a code unit-grid. Data were analysed using quantitative methodologies. For class '1ʹ and '2ʹ, an increase in engagement and a decrease in disruptive behaviour was observed at the implementation of intervention B1 compared to baseline A1 (p < 0.001). Likewise, an increase in engagement and a decrease in disruptive behaviour was observed in the second implementation of intervention B2 compared to baseline A2 and A1 (p < 0.001). The implementation of the opportunity of choice at the class-wide level for the two physical activity self-contained classes yielded an increased engagement rate and a decrease in disruptive behaviour.